Housing and welfare in Southern Europe - Allen, Judith, 1945- (Oxford ; Malden, MA : Blackwell Pub., 2004)
The growing literature on comparative European housing policy has played a major part in developing our understanding of the way housing in provided in different countries, and in the way the interaction between the stat, market and civil society is conceptualized. However, much of this analysis is rooted without question in the welfare states of northern Europe - there has been almost no research published in English on the provision of housing in southern Europe. Such research as exists deals with specific feature of housing policy, invariably in a single country. There is probably a.
New conditions and changing context for family solidarityConclusion: Family solidarity, housing and social cohesion; 6 Public Action in Housing; Concepts; Ideologies, political systems and conception of public action in housing; Distinctive features of public action in housing in southern Europe; Conclusions: public action versus state action; 7 Conclusions; The distinctiveness of southern European housing systems; Theorising housing provision: lessons from southern Europe; The future of southern housing systems; References; Index
Includes bibliographical references (pages 199-210) and index.
Print version record.
English.
John Wiley and Sons
Keywords: Housing -- Europe, Southern; Public welfare -- Europe, Southern; Families -- Europe, Southern; Housing policy -- Europe, Southern; Housing -- Europe -- Cross-cultural studies; Aide sociale; Familles; Logement -- Politique gouvernementale; Families; Housing; Housing policy; Public welfare; Europe; Southern Europe; Cross-cultural studies